Cutaneous Disorder Associated Diabetes Mellitus - Dina A, Dalimunthe; Dewi, Sisilia K (CoinReads Media Prima, 2025)
Diabetes mellitus (DM) is a chronic disease that occurs in nearly all countries, with complications related to skin disorders affecting up to 30% of diabetic patients. Skin changes in DM or as a complication of DM represent a complex and multifactorial process. These changes can occur through various pathomechanisms due to pathological glucose levels, resulting in alterations to skin aspects and clinical manifestations. The skin changes arise from diverse factors, including lesions related to Diabetes Mellitus, infection, manifestations of Diabetes Mellitus complications, and lesions resulting from Diabetes Mellitus treatment. This review will examine the clinical manifestations, pathophysiology and general management of several skin manifestations in diabetic patients.